2015
DOI: 10.1038/srep08068
|View full text |Cite
|
Sign up to set email alerts
|

Differential mechanisms of asparaginase resistance in B-type acute lymphoblastic leukemia and malignant natural killer cell lines

Abstract: Bacterial L-asparaginase (ASNase), hydrolyzing L-asparagine (Asn), is an important drug for treating patients with acute lymphoblastic leukaemia (ALL) and natural killer (NK) cell lymphoma. Although different native or pegylated ASNase-based chemotherapy are efficient, disease relapse is frequently observed, especially in adult patients. The neo-synthesis of Asn by asparagine synthetase (AsnS) following ASNase treatment, which involves the amino acid response and mitogen-activated protein kinase kinase/extrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 47 publications
(67 reference statements)
0
25
0
Order By: Relevance
“…Indeed, different formulations of L-asparaginase have been an integral part of the treatment for acute lymphoblastic leukemia for many years [22]. Resistance to L-asparaginase treatment is often accompanied by up-regulation of ASNS [10, 11, 23, 24]. Therefore, means to inhibit ASNS enzyme activity or synthesis are considered to be helpful to counteract evolving resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, different formulations of L-asparaginase have been an integral part of the treatment for acute lymphoblastic leukemia for many years [22]. Resistance to L-asparaginase treatment is often accompanied by up-regulation of ASNS [10, 11, 23, 24]. Therefore, means to inhibit ASNS enzyme activity or synthesis are considered to be helpful to counteract evolving resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is growing evidence that this view is too simplistic [11] and recent research shows that L-asparaginase might be useful for the treatment of solid malignancies as well [12]. In our study, we focused on glioblastoma WHO IV, which is the most common primary brain tumor in adults and bears a grim prognosis with median survival rates of less than 1.5 years [13].…”
Section: Introductionmentioning
confidence: 99%
“…[10] Asparaginase depletes serum levels of asparagine, effectively depriving leukemia cells of this critical amino acid. [10] Although the relationship between asparagine-synthetase expression and outcomes remains controversial, [11][12][13] it has been shown that continuous and prolonged asparagine depletion is associated with improved outcomes. [6] In a study of 377 pediatric patients treated on a Dana-Farber Cancer Institute (DFCI) protocol, investigators found superior outcomes for patients who completed !26 consecutive weeks of asparaginase treatment compared with patients who received <26 weeks (90 ± 2% vs. 73 ± 7%; p < .01).…”
Section: Asparaginase Backgroundmentioning
confidence: 99%
“…Taken together, these reports and our findings suggest that GLS could be a biomarker of Gln dependence and a therapeutic target. In contrast, another report stated that changes in the expression of apoptosis‐regulatory genes (especially NF‐κB‐related genes) are associated with L‐ASNase susceptibility in B‐ALL cell lines . These findings therefore suggest that multiple factors other than Asn‐dependency and ASNS, including GLS1, can influence L‐ASNase action and susceptibility depending on the cellular context .…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, another report stated that changes in the expression of apoptosis‐regulatory genes (especially NF‐κB‐related genes) are associated with L‐ASNase susceptibility in B‐ALL cell lines . These findings therefore suggest that multiple factors other than Asn‐dependency and ASNS, including GLS1, can influence L‐ASNase action and susceptibility depending on the cellular context . Future studies using clinical samples may provide insights for the precise mechanisms of L‐ASNase in ALL and malignant lymphoma.…”
Section: Discussionmentioning
confidence: 91%